NETWORK TRAFFIC ANALYSIS WITH GENETIC ALGORITHMS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the possibilities of using genetic algorithms in detecting network attacks. The genetic algorithm improves efficiency in selecting network attributes and adjusting model parameters as an optimization method based on evolutionary principles. The study highlighted the most important traits through selection, cross-over, and mutation mechanisms, resulting in improved attack accuracy by up to 97%. As a result, the genetic approach significantly improves the accuracy of the IDS system.